Relation of Gamma-Glutamyl Transferase to Cardiovascular Events in Patients with Acute Coronary Syndromes - Ndrepepa, Gjin; Braun, Siegmund; Cassese, Salvatore; Fusaro, Massimiliano; Laugwitz, Karl-Ludwig; Schunkert, Heribert; Kastrati, Adnan (American Journal of Cardiology, 2016)
The prognostic value of gamma-glutamyl transferase (GGT) in patients with acute coronary syndromes (ACS) has been incompletely investigated. We investigated this clinically relevant question in 2,534 consecutive patients with ACS who underwent percutaneous coronary intervention (PCI). GGT activity was measured before PCI procedure in all patients. Statin therapy at hospital discharge was prescribed in 94% of the patients. The primary outcome was 3-year mortality. Patients were divided into 3 groups: the group with GGT in the first tertile (GGT <28 U/L; n = 848 patients), the group with GGT in the second tertile (GGT 28 to <50 U/L; n = 843 patients), and the group with GGT in the third tertile (GGT ≥50 U/L; n = 843 patients). The primary outcome (all-cause deaths) occurred in 250 patients: 70 deaths (9.7%) among patients of the first, 69 deaths (9.0%) among patients of the second, and 111 deaths (14.8%) among patients of the third GGT tertile (adjusted hazard ratio [HR] 1.24, 95% CI 1.08 to 1.42, p = 0.002) and cardiac and noncardiac deaths occurred in 157 (63%) and 93 patients (37%), respectively. GGT was associated with the increased risk of noncardiac mortality (adjusted HR 1.35 [1.09 to 1.66], p = 0.005) but not cardiac mortality (adjusted HR 1.16 [0.97 to 1.38], p = 0.098; all 3 risk estimates were calculated per SD increase in the logarithmic scale of GGT activity). In conclusion, in contemporary patients with ACS treated with PCI and on statin therapy, elevated GGT activity was associated with the increased risk of all-cause and noncardiac mortality but not with the risk of cardiac mortality.
CRIS-Team Scopus Importer:2023-03-08